Interaction between Biological Nitrogen Removal Processes and Operating Parameters: A Review - Mozumder, M. S. I.; Hossain, M. D. (Journal of Scientific Research, 2020)
Nitrogen, mostly in the form of ammonia or nitrate containing wastewater deteriorated the water quality which simultaneously affects environment, plants, animals and human life. A number of researchers nowadays are conducting research to find out efficient and cost effective nitrogen removal technique along with optimum operating parameters. It is very important to uncover the optimum range of each parameter. In this study, it was winnowed to elicit the optimum operating ranges of dissolved oxygen concentration, temperature, pH, free ammonia concentration, nitrate concentration and culture medium. The nitrogen removal techniques were compared, evaluated considering advantages and disadvantages of them. Partial nitrification combined with anaerobic ammonium oxidation was found most prospective nitrogen removal technique for wastewater treatment compare to other techniques (conventional nitrification-denitrification over nitrate/nitrite, anammox, SND etc.) due to less oxygen consumption (62.5 % less), less sludge production, no carbon requirement, single reactor used and energy efficiency. SND process was more economical due to faster consumption of ammonia, nitrite and nitrate. There was various culture mediums which had a favorable or detrimental effect on specific nitrogen removal processes. However for desired bacteria culture for specific application, suitable culture medium needs to be selected considering the optimal operating parameters for microbial growth.